Determinants of Drug Resistance in B-Cell Non-Hodgkin Lymphomas: The Case of Lymphoplasmacytic Lymphoma/Waldenström Macroglobulinemia - Piazza, Francesco; Di Paolo, Veronica; Scapinello, Greta; Manni, Sabrina; Trentin, Livio; Quintieri, Luigi (Frontiers in Oncology, 2022)
Lymphoplasmacytic lymphoma (LPL) is a rare subtype of B cell-derived non-Hodgkin lymphoma characterized by the abnormal growth of transformed clonal lymphoplasmacytes and plasma cells. This tumor almost always displays the capability of secreting large amounts of monoclonal immunoglobulins (Ig) of the M class (Waldenström Macroglobulinemia, WM). The clinical manifestations of WM/LPL may range from an asymptomatic condition to a lymphoma-type disease, or a clinical picture dominated by IgM paraprotein-related symptoms. Despite the substantial progresses achieved over the last years in the therapy of LPL/WM, this lymphoma is still almost invariably incurable and exhibits a propensity towards the development of refractoriness to therapy. Patients who have a progressive disease are often of difficult clinical management and novel effective treatments are eagerly awaited. In this review, we describe the essential clinical and pathobiological features of LPL/WM and analyze the current knowledge on the mechanisms of drug resistance in this disease, by concisely focusing on conventional drugs, monoclonal antibodies and novel agents, chiefly Bruton’s Tyrosine Kinase (BTK) inhibitors. The implications of molecular lesions as predictors of response or as a warning for the development of therapy resistance are highlighted.